Survey of Blood and Urine Biological at Petrochemical firefighters - Saber, Elham (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Firemen have one of the most dangerous and hazardous jobs which is associated with high levels of physical stress, heart arrest, different types of strains, and many accidents. According to the National Fire Protection Agency, the death rate of firemen who lost their lives during emergency operations was 56 between 1990 and 2000. Materials and Methods: This descriptive, analytical study was carried out on 89 firemen working in a petrochemical plant. To compare the level of firemen’s blood factors with normal levels, a confidence interval of 95% was set. SPSS software (version 16) was used to analyze the data, and the cut-off point of.05 was considered as statistically significant. Random sampling was employed, and the data were based on firemen’s medical examination and test profiles. Results: The average body mass index of the firemen was 25.3 with its maximum and minimum being 39 and 16.2, respectively. The most abnormal factor in firemen’s blood was the cholesterol which was higher than the normal range. Conclusion: The findings showed that the most common diseases among the firemen were high Cholesterol and high aspartate transaminase which could be the result of long sedentary positions and exposure to chemicals.